Does Increased State Pharmacy Regulatory Burden Lead to Better Public Safety Outcomes? - Alex Adams; Jennifer Adams (University of Minnesota Libraries Publishing, 2021)
Pharmacy has traditionally been a highly regulated profession. In a recent study, the state with the largest pharmacy regulatory word count had 6.7 times as many words as the state with the lowest word count. Given the wide variation in state pharmacy regulations, this paper seeks to spark discussion on how we can assess public safety outcomes in states based on the overall volume of pharmacy regulation with a focus on: 1) fitness to practice; 2) controlled substance outcomes; and 3) compounding safety. In examining these categories, existing data sources are limited and suboptimal, though formal disciplinary actions against pharmacy licensees are very infrequent. Thus, it seems preferable for states to have a regulatory framework that allows boards of pharmacy to deal with the rare public safety issues that occur, while not holding back the vast majority of pharmacists from practicing to the top of their education and training.